Tumor-derived exosomes promote the in vitro osteotropism of melanoma cells by activating the SDF-1/CXCR4/CXCR7 axis - Francesco Mannavola; Marco Tucci; Claudia Felici; Anna Passarelli; Stella D’Oronzo; Francesco Silvestris (Journal of Translational Medicine, 2019)
Abstract Background Bone metastases occur rarely in patients suffering from malignant melanoma, although their onset severely worsens both prognosis and quality of life. Extracellular vesicles (EVs) including exosomes (Exos) are active players in melanoma progression involved in the formation of the pre-metastatic niche. Methods Trans-well assays explored the basal migratory and invasive potential of four melanoma cell lines and investigated their different propensity to be attracted toward the bone. Exosomes were purified from cell supernatants by ultracentrifugation and explored in their ability to influence the bone tropism of melanoma cells. The molecular machinery activated during this process was investigated by RT-PCR, droplet digital-PCR, flow-cytometry and Western blot, while loss of function studies with dedicated siRNAs defined the single contribute of CXCR4 and CXCR7 molecules. Results Melanoma cells revealed a variable propensity to be attracted toward bone fragments. Gene profiling of both osteotropic and not-osteotropic cells did not show a different expression of those genes notoriously correlated to chemotaxis and bone metastasis. However, bone conditioned medium significantly increased CXCR4, CXCR7 and PTHrP expression solely to osteotropic cells, while their Exos were able to revert the original poor bone tropism of not-osteotropic cells through CXCR7 up-regulation. Silencing experiments also demonstrated that membrane expression of CXCR7 is required by melanoma cells to promote their chemotaxis toward SDF-1 gradients. Conclusions Our data correlated the osteotropism of melanoma cells to the activation of the SDF-1/CXCR4/CXCR7 axis following the exposition of tumor cells to bone-derived soluble factors. Also, we demonstrated in vitro that tumor-derived Exos can reprogram the innate osteotropism of melanoma cells by up-regulating membrane CXCR7. These results may have a potential translation to future identification of druggable targets for the treatment of skeletal metastases from malignant melanoma.